The Fijian Colonial Experience: A study of the neotraditional order under British colonial rule prior to World War II - J. MacNaught, Timothy (ANU Press, 2016)
Indigenous Fijians were singularly fortunate in having a colonial administration that halted the alienation of communally owned land to foreign settlers and that, almost for a century, administered their affairs in their own language and through culturally congenial authority structures and institutions. From the outset, the Fijian Administration was criticised as paternalistic and stifling of individualism. But for all its problems it sustained, at least until World War II, a vigorously autonomous and peaceful social and political world in quite affluent subsistence - underpinning the celebrated exuberance of the culture exploited by the travel industry ever since.